2003
DOI: 10.1063/1.1540719
|View full text |Cite
|
Sign up to set email alerts
|

Long afterglow phosphorescent sensor materials for fiber-optic thermometer

Abstract: Development of erbium-doped silica sensor probe for fiber-optic fluorescence thermometer Rev. Sci. Instrum. 76, 094902 (2005); 10.1063/1.2038508 Low temperature fluorescence thermometer application of long afterglow phosphorescent Sr Al 12 O 19 : Eu 2 + , Dy 3 + crystals Rev. Sci. Instrum. 76, 084901 (2005); 10.1063/1.1988147 Fiber-optic thermometer using Cr-doped YAlO 3 sensor head Rev. Sci. Instrum. 74, 3883 (2003); 10.1063/1.1589582 Fabrication of ruby sensor probe for the fiber-optic thermometer using fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
33
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 11 publications
1
33
0
Order By: Relevance
“…Recently, we have proposed an application of the long afterglow SrAl 2 O 4 :Eu,Dy phosphors for a sensor head because the afterglow phosphorescent characteristics of the intensity and decay time depend dramatically on the ambient temperature [4]. Moreover, the thin film fabrication of this long afterglow SrAl 2 two-dimensional temperature sensing by the scanning of the excitation light and the monitoring the afterglow characteristics depending on the temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have proposed an application of the long afterglow SrAl 2 O 4 :Eu,Dy phosphors for a sensor head because the afterglow phosphorescent characteristics of the intensity and decay time depend dramatically on the ambient temperature [4]. Moreover, the thin film fabrication of this long afterglow SrAl 2 two-dimensional temperature sensing by the scanning of the excitation light and the monitoring the afterglow characteristics depending on the temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Guo et al [23] reported the enhancement mechanism of luminescent properties of RE 3+ (RE 3+ = Eu 3+ , Sm 3+ , Dy 3+ ) in Y 2 O 2 S phosphor by a trace of Tb 3+ . Aizawa et al [24] reported the SrAl 2 O 4 :Eu 2+ phosphor doped with Nd, Sm, Lu, Gd, Dy and Y, and found that the long afterglow phosphorescence was influenced by the depth and density of the traps. Chen et al [1] reported that the luminescent properties of SrAl 2 O 4 :Eu 2+ , Dy 3+ could be significantly modified by the Yb 3+ ions doping.…”
Section: Introductionmentioning
confidence: 98%
“…Long afterglow phosphorescent SrAl 2 O 4 crystals including traps with high concentration are found to be a highly sensitive sensor head material with long temperature coefficient [8,9]. The high temperature coefficient of a SrA1 2 O 4 based sensor head is due to the thermal excitation process of trapped carriers at the trap levels with E ¼ 0:5 eV [8,9].…”
Section: Introductionmentioning
confidence: 98%
“…The high temperature coefficient of a SrA1 2 O 4 based sensor head is due to the thermal excitation process of trapped carriers at the trap levels with E ¼ 0:5 eV [8,9]. In addition to SrAl 2 O 4 phosphors, Eu doped CaAl 2 O 4 co-doped with rare earth elements as the auxiliary activators are also expected to be highly sensitive sensor head materials because of their high trap density.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation